Wyjazdy studentów w ramach programu Erasmus jako instytucjonalna forma przedłużonego moratorium. Przyczynek do tezy o "kryzysie ćwierćwiecza" = Students` Exchange within the Erasmus Programme as an Institutional Form of the Extended Moratorium. Contribution to the Thesis of Quarter-Century Crisis - Rachowska, Zuzanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
programme in order to finish building their own self in a reflective way. It especially applies to students who, despite the age indicating the completion of an identity crisis, remain in an extended moratorium on early adulthood - experience the "quarter-century crisis". The crisis manifests itself in the escape from making commitments assigned to conventionally defined adulthood.
Keywords: Erasmus; wymiana studentów; młodzi dorośli; studenci